2019
DOI: 10.1002/jcph.1557
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cannabis and Interactions With Anticoagulant and Antiplatelet Agents

Abstract: Legalization of medical cannabis has occurred in 33 states and the District of Columbia, and recreational use has increased exponentially since 2013. As a result, it is important to understand how cannabis interacts with other drugs and has potential risks for patients on concomitant medications. Components of medical cannabis can inhibit or compete for several cytochrome P450 (CYP) hepatic isoenzymes, UDP‐glucuronosyltransferases, and P‐glycoprotein. These enzymes and transporters are involved in the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Similar to the results from this review, the interaction between Cannabis Sativa L. and warfarin was classified as major and possible. In addition, Greger et al [ 42 ], in a review of warfarin interactions, found in vivo evidence (case reports) regarding cannabis–warfarin interactions, and theorized similar interactions, for example, with clopidogrel, based on the isoenzymes that metabolize this drug and cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the results from this review, the interaction between Cannabis Sativa L. and warfarin was classified as major and possible. In addition, Greger et al [ 42 ], in a review of warfarin interactions, found in vivo evidence (case reports) regarding cannabis–warfarin interactions, and theorized similar interactions, for example, with clopidogrel, based on the isoenzymes that metabolize this drug and cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that cannabis use disorders are emerging among older French adults 32 . This calls for some caution because the elderly take medications that can interact with cannabis, such as anticoagulants 33 …”
Section: Discussionmentioning
confidence: 99%
“…Published case reports are another opportunity to gather data. For example, there have been case reports highlighting potential drug interactions between cannabis and warfarin 34 . It is highly likely that RWD digital repositories and methods of data collection will become more prominent in the future.…”
Section: Rwe Sources and Challengesmentioning
confidence: 99%
“…Published case reports are another opportunity to gather data. For example, there have been case reports highlighting potential drug interactions between cannabis and warfarin 34. It is highly likely that RWD digital repositories and methods of data collection will become more prominent in the future.3 | RWE IMPACT: POLICY AND REGULATORY DECISION MAKINGEvidence-based clinical practice and regulatory decision making have historically relied on gold-standard RCT data 5.…”
mentioning
confidence: 99%